Theoretical and Methodological Trends in Public Sector Accounting Research (2017–2022): A Structured Literature Review of Six International Journals - Nashirotun Nisa Nurharjanti (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2025)
This study maps the trend of using theory and methodological approaches in public sector accounting research between 2017 and 2022. This research was conducted with a journal-bound sampling design from six international journals that consistently publish public sector accounting research. The total number of articles tabulated during the observation period was 975 articles. For the theory mapping, articles were screened based on the criteria of "explicit use of theory as an analytical framework", so 340 articles were analyzed. For methodological mapping, all articles in the journal sample were classified at the approach level (qualitative, quantitative, and mixed). The mapping results show that Institutional Theory is the most frequently used theory in almost all journals, while qualitative approach dominates in public sector accounting research publications. These findings confirm the importance of institutional context in public sector studies and show room for the development of the use of alternative theories as well as the expansion of methodological designs.